Fine ceramics (advanced ceramics, advanced technical ceramics). Reinforcement of ceramic composites. Determination of distribution of tensile strength and tensile strain to failure of filaments within a multifilament tow at ambient temperature. (20th September 2022) - British Standards Institution,
No abstract available